2021
DOI: 10.3390/s21082805
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Selected Spatio-Temporal Gait Parameters on Subjects with Pronated Foot Posture on the Basis of Measurements Using OptoGait. A Case-Control Study

Abstract: Walking is part of daily life and in asymptomatic subjects it is relatively easy. The physiology of walking is complex and when this complex control system fails, the risk of falls increases. As a result, gait disorders have a major impact on the older adult population and have increased in frequency as a result of population aging. Therefore, the OptoGait sensor is intended to identify gait imbalances in pronating feet to try to prevent falling and injury by compensating for it with treatments that normalize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
3
5
0
Order By: Relevance
“…The data obtained is consistent with other research where it was reported that gait parameters were altered in subjects with CLBP for fear of pain or by an unstable gait [ 2 , 5 , 17 , 21 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The data obtained is consistent with other research where it was reported that gait parameters were altered in subjects with CLBP for fear of pain or by an unstable gait [ 2 , 5 , 17 , 21 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Sensors technology is used to evaluate the kinematics of gait and physical activity (mobile phones, accelerometers, video recording systems, three-dimensional sensors, etc.) [ 5 , 20 , 21 ]. The OptoGait sensor system is commonly used to accurately monitor spatiotemporal gait patterns and, thus, compensating for alterations involving a deficit in motor control and balance before and after an intervention [ 2 , 5 , 7 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations